2017
DOI: 10.5812/iranjradiol.41485
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Renal Cortical Involvement Using Serum and Urinary Inflammatory Markers in Children with Febrile Urinary Tract Infection

Abstract: Background: Erythrocyte sedimentation rate (ESR), serum C-reactive protein (CRP), urinary β2 microglobulin, antibody-coated bacteria in the urine sediment, and urinary lactic dehydrogenase (LDH) are more traditional tests used to diagnose true pyelonephritis. Acute-phase dimercaptosuccinic acid (DMSA) scan is a sensitive method for diagnosis of true pyelonephritis. Objectives:Defining predictive values of traditional inflammatory serologic parameters, urine analysis indexes, kidney ultrasonography and fever in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Multiple research projects reported that pediatric patients with chronic constipation often concurrently suffer from RUTI and pyelonephritis. These patients frequently had diverse kidney and urinary tract anatomical abnormalities revealed through X-ray and ultrasonographic examination [142,151,152]. Longstanding constipation has the potential to alter the detrusor muscle activity of the urinary bladder and augment excitatory serotoninergic function, increasing the likelihood of enuresis or urine incontinence [143,[153][154][155][156].…”
Section: Impact Of Constipationmentioning
confidence: 99%
“…Multiple research projects reported that pediatric patients with chronic constipation often concurrently suffer from RUTI and pyelonephritis. These patients frequently had diverse kidney and urinary tract anatomical abnormalities revealed through X-ray and ultrasonographic examination [142,151,152]. Longstanding constipation has the potential to alter the detrusor muscle activity of the urinary bladder and augment excitatory serotoninergic function, increasing the likelihood of enuresis or urine incontinence [143,[153][154][155][156].…”
Section: Impact Of Constipationmentioning
confidence: 99%